2019
DOI: 10.3389/fgene.2019.00893
|View full text |Cite
|
Sign up to set email alerts
|

Genome Diversity and Signatures of Selection for Production and Performance Traits in Dromedary Camels

Abstract: Dromedary camels (Camelus dromedarius) are single-humped animals found throughout the deserts of Africa, the Arabian Peninsula, and the southwest of Asia. This well-adapted species is mainly used for milk and meat production, although some specific types exhibit superior running performance and are used in racing competitions. However, neither performance nor production camels are bred under intensive genomic selection programs with specific aims to improve these traits. In this study, the full genome sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 74 publications
3
33
0
Order By: Relevance
“…Principal component analysis suggested that Sudanese camel populations are almost homogeneous [11]. On the contrary, PCA results distinguished the Chinese Bactrian camels from the Mongolian Bactrian camels very well [31].…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Principal component analysis suggested that Sudanese camel populations are almost homogeneous [11]. On the contrary, PCA results distinguished the Chinese Bactrian camels from the Mongolian Bactrian camels very well [31].…”
Section: Discussionmentioning
confidence: 84%
“…Heterozygosity of the Iranian central desert dromedaries was predicted as low (0.25 ± 0.30). Arabian Peninsula and Sudanese dromedaries' H O where 0.560 ± 0.003 and 0.347 ± 0.003, respectively [11]. The camels sampled from the central desert of Iran have higher relationships than dromedaries from Sudan (median A jk = − 0.007 ± 0.018) and lower ones than individuals from the Arabian Peninsula (median A jk = 0.347 ± 0.093) [11].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…For example, genotyping-by-sequencing (GBS) on livestock has been a sufficient solution that is required for population genetic and genomic studies [15]. This method has been successfully used to identify selection signatures of important economic traits in cattle [16], pigs [17,18], chicken [19], and camels [20]. The goal of this investigation was to perform a pair-wise marker differentiation comparison in a genome-wide scan between Noire de Thibar and Queue fine de l'ouest Tunisian sheep breeds, using genotyping-by-sequencing data to reveal putative regions under strong and recent selection.…”
Section: Introductionmentioning
confidence: 99%